Environment-friendly high-strength thermal insulation castable for coke oven bottom
By applying environmentally friendly high-strength insulation castables in the coke oven bottom, the problem of low mechanical strength of existing light-weight insulation castables is solved, and higher mechanical strength and insulation performance are achieved. It is suitable for coke oven bottom in high-temperature environments application.
Patent Information
- Application Number
- CN202411596405.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The existing lightweight insulation castables have the problem of low mechanical strength in coke oven bottom applications, which is difficult to meet the needs of high strength and efficient insulation.
Using environmentally friendly high-strength coke oven furnace bottom insulation castable, mullite porous clinker, ultrafine silicon powder, aluminate cement, deionized water and admixtures (composed of functional cementitious agent and modified carbon fibers) ) Mix in a specific proportion and processed through pressurized molding, curing and baking.
It significantly improves the mechanical strength and insulation performance of the insulation castable, can more effectively support the high-temperature environment of the coke oven bottom, extend the service life and reduce energy consumption.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of refractory materials, and more specifically, to an environmentally friendly high-strength thermal insulation castable for a coke oven bottom. Background Art
[0002] A coke oven is an industrial furnace used to produce metallurgical coke, and is widely used in the fields of steel, chemical industry, etc. Among them, the coke oven bottom is an important part of the coke oven structure. It supports the coke and the charge, prevents them from collapsing or leaking, and maintains the heat and chemical reaction in the oven. In order to prevent the heat loss of the coke oven during operation, improve the quality of coke and save energy, the thermal insulation performance of the coke oven bottom is often improved by adding thermal insulation castings.
[0003] Among them, lightweight thermal insulation castables have excellent thermal insulation performance and good chemical stability. It is widely used as thermal insulation castable for coke oven bottom. However, lightweight thermal insulation castable has the problem of low mechanical strength. Summary of the invention
[0004] In order to solve the problems mentioned in the above background technology, the present application provides an environmentally friendly high-strength thermal insulation castable for coke oven bottom.
[0005] Environmentally friendly high-strength coke oven bottom insulation castable is prepared by the following steps: Step S1, prepare the following raw materials in parts by weight: 40-50 parts of mullite porous clinker, 8-10 parts of ultrafine silica powder, 12-16 parts of aluminate cement, 2-6 parts of deionized water, and 0.2-0.4 parts of admixture; Step S2, pressure molding: Mullite porous clinker, ultrafine silica powder and aluminate cement are mixed, deionized water is added, stirred evenly, admixtures are added, stirring is continued for 12-16 minutes, pressure molding is performed, curing is performed, and baking is performed to obtain an environmentally friendly high-strength thermal insulation castable for coke oven bottom.
[0006] Preferably, the particle size of the ultrafine silicon powder is ≤0.015 mm.
[0007] Preferably, the admixture consists of a functionalized binder and modified carbon fibers, wherein the functionalized binder accounts for 72-84% and the rest is modified carbon fibers.
[0008] Preferably, the pressure of the pressurized molding is 150-180 kg / m 2 ; The pressure molding time is 10-20s.
[0009] Preferably, the functionalized binder is prepared by the following steps: Step A1, carbon tetrachloride and anhydrous THF are mixed evenly, dibutyl phosphite is added, and triethylamine and diethanolamine are added under an ice-water bath, the temperature is raised to 45-55° C., the reaction is stirred for 8-10 hours, suction filtered, and the filtrate is rotary evaporated to obtain a hydroxy phosphate compound, wherein the mass ratio of carbon tetrachloride, anhydrous THF, dibutyl phosphite, triethylamine and diethanolamine is 60-70:30-40:5-7:1.8-2.2:3.8-5.4. In the above reaction process, dibutyl phosphite and diethanolamine are used as raw materials to obtain a hydroxy phosphate compound containing a hydroxyl group through a Michael addition reaction; Step A2, adding silane coupling agent KH-550 and 4-hydroxyphthalic anhydride to anhydrous THF, stirring evenly, heating to reflux, stirring and reacting for 4-6 hours to obtain a modified solution, ultrasonically dispersing nano-silica in anhydrous THF, adding the modified solution and deionized water, heating to 52-56° C., stirring for 4-5 hours, after the stirring is completed, suction filtering, washing the filter cake, and drying to obtain carboxylated silica; adding carboxylated silica, p-toluenesulfonic acid and hydroxyphosphate compound to anhydrous DMF, heating to 35-45° C., stirring evenly, then heating to 72-80° C., continuing to stir and react for 6-8 hours, rotary evaporation, washing, and drying to obtain esterified Monomers, wherein the mass ratio of silane coupling agent KH-550, 4-hydroxyphthalic anhydride and anhydrous DMF is 2-4: 1.5-2.9: 30-40, the mass ratio of nano-silica, anhydrous THF, modified liquid and deionized water is 3-5: 45-55: 16-20: 6-8, the mass ratio of carboxylated silica, p-toluenesulfonic acid, hydroxy phosphate compound and anhydrous DMF is 2-3: 0.02-0.04: 1.6-2.4: 55-65, and the amount of the hydroxy phosphate compound is controlled to be slightly higher than that of the carboxylated silica, so that after the reaction is completed, there are still remaining hydroxyl groups that can participate in the subsequent reaction process; Step A3, ultrasonically disperse the esterification monomer in anhydrous DMF, raise the temperature to 64-68°C while stirring, then add triethylamine and toluene, add epichlorohydrin dropwise, stir and react for 3-4 hours after the addition is complete, filter and rotary evaporate after the reaction is complete, dissolve the rotary evaporated product in acetone, filter, and rotary evaporate the filtrate to obtain a functionalized binder, wherein the mass ratio of the esterification monomer, anhydrous DMF, triethylamine, toluene, epichlorohydrin and acetone is 42-64:520-640:2.8-4.6:6-12:22-26:320-360, and in the above reaction process, with anhydrous DMF as solvent, triethylamine as catalyst, and toluene as dehydrating agent, the hydroxyl group on the esterification monomer undergoes a nucleophilic substitution reaction with the chlorine atom on the epichlorohydrin to obtain a functionalized binder.
[0010] Preferably, the modified carbon fiber is prepared by the following steps: The carbon fiber is placed in acetone, stirred at 45-55°C for 8-12 hours, then taken out and washed to obtain pretreated carbon fiber. The pretreated carbon fiber is placed in an aqueous nitric acid solution, stirred at 80-90°C for 2-3 hours, filtered, and the filter cake is washed until the washing liquid is neutral to obtain modified carbon fiber, wherein the mass ratio of carbon fiber to acetone is 3-5:40, and the mass ratio of pretreated carbon fiber to aqueous nitric acid solution is 5:50-60. Acetone is used to wash to remove impurities on the surface of the carbon fiber, and then it is oxidized with concentrated nitric acid to increase the oxygen-containing groups on the surface of the carbon fiber.
[0011] Preferably, the mass fraction of the nitric acid aqueous solution is 66-68%.
[0012] Compared with the prior art, the present invention has the following beneficial effects: In order to improve the thermal insulation performance and mechanical strength of the thermal insulation castable, the present application adds an admixture, which is composed of a functionalized binder and modified carbon fiber. The functionalized binder contains a phosphate group, an ester group, a benzene ring, a nano-silica structure and an epoxy group. The presence of the phosphate group and the ester group can produce multiple hydrogen bonds with the surface of the cement hydration product and the active hydroxyl group of the modified carbon fiber, and the large steric hindrance of the rigid benzene ring improves the mechanical strength of the castable. The existence of the nano-silica structure, on the one hand, exerts the excellent mechanical properties and thermal stability of the inorganic particles themselves, and on the other hand, On the one hand, the silanol groups on nano-silica can also produce multiple hydrogen bonds with the active hydroxyl groups on the surface of cement hydration products and modified carbon fibers, thereby improving their compatibility while further improving the thermal insulation properties and mechanical strength of the castable. The presence of epoxy groups can chemically cross-link with the active hydroxyl groups on the surface of cement hydration products and modified carbon fibers, further improving the thermal insulation properties and mechanical strength of the castable. The presence of carbon fibers plays its own reinforcing and toughening role, and through the synergistic effect of functionalized binders and modified carbon fibers, the thermal insulation properties and mechanical strength of the castable are improved. DETAILED DESCRIPTION
[0013] In order to make the implementation methods of the present application easier to understand, the present application will be described in detail below in conjunction with specific examples. These examples are only for illustration and are not limited to the scope of application of the present application.
[0014] The contents of the main raw materials and their components used in the examples and comparative examples are as follows: The porous mullite clinker is produced by Zibo Baoxing Industry and Trade Co., Ltd., with a compressive strength of 55MPa and a refractory temperature of 1700℃. The ultrafine silica powder is 325 mesh quartz powder industrial grade high-purity ultrafine whiteness ceramic silica powder produced by Lingshou Yongshun Mineral Products Processing Plant, with a melting point of 1750℃. The aluminate cement is the Kerui Refractory Brand CA-60 refractory cement produced by Zhengzhou Kerui Refractory Materials Co., Ltd., with a thermal conductivity of 0.030-0.035W / (m·K) and a flexural strength of 2.5-10.0MPa. The carbon fiber is chopped carbon fiber produced by Carboene Technology (Shenzhen) Co., Ltd., with a diameter of 7µm.
[0015] The present application is further described in detail below in conjunction with embodiments and comparative examples.
[0016] Preparation Examples 1-3 and Comparative Preparation Example 1 provide methods for preparing modified carbon fibers.
[0017] Preparation Example 1 This preparation example provides a method for preparing a modified carbon fiber, and the modified carbon fiber is prepared by the following steps: The carbon fiber was placed in acetone, stirred at 45°C and 500 rpm for 8 hours, then taken out and washed to obtain pretreated carbon fiber. The pretreated carbon fiber was placed in an aqueous nitric acid solution, stirred at 80°C and 600 rpm for 2 hours, filtered, and the filter cake was washed with deionized water until the washing liquid was neutral to obtain modified carbon fiber, wherein the mass ratio of carbon fiber to acetone was 3:40, the mass ratio of pretreated carbon fiber to aqueous nitric acid solution was 5:50, and the mass fraction of aqueous nitric acid solution was 66%.
[0018] Preparation Example 2 This preparation example provides a method for preparing a modified carbon fiber, and the modified carbon fiber is prepared by the following steps: The carbon fiber was placed in acetone, stirred at 50°C and a rotation speed of 550 rpm for 10 hours, then taken out and washed to obtain pretreated carbon fiber. The pretreated carbon fiber was placed in an aqueous nitric acid solution, stirred at 85°C and a rotation speed of 650 rpm for 2.5 hours, filtered, and the filter cake was washed with deionized water until the washing liquid was neutral to obtain modified carbon fiber, wherein the mass ratio of carbon fiber to acetone was 4:40, the mass ratio of pretreated carbon fiber to aqueous nitric acid solution was 5:55, and the mass fraction of aqueous nitric acid solution was 67%.
[0019] Preparation Example 3 This preparation example provides a method for preparing a modified carbon fiber, and the modified carbon fiber is prepared by the following steps: The carbon fiber was placed in acetone, stirred at 55°C and 550 rpm for 12 hours, then taken out and washed to obtain pretreated carbon fiber. The pretreated carbon fiber was placed in an aqueous nitric acid solution, stirred at 90°C and 700 rpm for 3 hours, filtered, and the filter cake was washed with deionized water until the washing liquid was neutral to obtain modified carbon fiber, wherein the mass ratio of carbon fiber to acetone was 5:40, the mass ratio of pretreated carbon fiber to aqueous nitric acid solution was 5:60, and the mass fraction of aqueous nitric acid solution was 68%.
[0020] Comparative Preparation Example 1 This comparative preparation example provides a method for preparing a modified carbon fiber, and the modified carbon fiber is prepared by the following steps: The carbon fiber was placed in acetone, stirred at 45°C and 500 rpm for 8 hours, then taken out and washed to obtain pretreated carbon fiber. The pretreated carbon fiber was placed in anhydrous ethanol, stirred at 80°C and 600 rpm for 2 hours, filtered, and the filter cake was washed with deionized water until the washing liquid was neutral to obtain modified carbon fiber, wherein the mass ratio of carbon fiber to acetone was 3:40, and the mass ratio of pretreated carbon fiber to anhydrous ethanol was 5:50.
[0021] Preparation Examples 4-6 and Comparative Preparation Examples 2-4 provide methods for preparing modified carbon fibers.
[0022] Preparation Example 4 This preparation example provides a method for preparing a functionalized binder, and the functionalized binder is prepared by the following steps: Step A1, stirring carbon tetrachloride and anhydrous THF at a rotation speed of 550 rpm for 25 minutes until uniform, adding dibutyl phosphite, and then adding triethylamine and diethanolamine under an ice-water bath, heating to 45° C., maintaining the rotation speed unchanged, stirring and reacting for 8 hours, filtering with suction, and rotary evaporating the filtrate to remove anhydrous THF, controlling the rotary evaporation temperature to 65° C. to obtain a hydroxy phosphate compound, wherein the mass ratio of carbon tetrachloride, anhydrous THF, dibutyl phosphite, triethylamine and diethanolamine is 60:30:5:1.8:3.8; Step A2, adding silane coupling agent KH-550 and 4-hydroxyphthalic anhydride to anhydrous THF, controlling the speed to 600 rpm, stirring for 20 minutes until uniform, heating to reflux, maintaining the speed unchanged, stirring for 4 hours to obtain a modified liquid, ultrasonically dispersing nano-silicon dioxide in anhydrous THF, controlling the ultrasonic frequency to 35 kHz, the ultrasonic power to 550 w, ultrasonic for 35 minutes, adding the modified liquid and deionized water, heating to 52 ° C, stirring at a speed of 650 rpm for 4 hours, after the stirring is completed, suction filtering, the filter cake is washed 3 times with anhydrous ethanol and deionized water, and dried at 50 ° C to constant weight to obtain carboxylated silica; adding carboxylated silica, p-toluenesulfonic acid and hydroxyphosphate compound In anhydrous DMF, the temperature was raised to 35°C, the rotation speed was controlled to 650rpm, and the mixture was stirred for 25min until uniform, and then the temperature was raised to 72°C, and the reaction was continued with stirring for 6h. The rotary evaporation temperature was controlled to 84°C, and the filtrate was subjected to rotary evaporation to remove anhydrous DMF, and then the mixture was washed with anhydrous ethanol and deionized water for 3 times in sequence, and dried at 55°C to constant weight to obtain an esterified monomer, wherein the mass ratio of silane coupling agent KH-550, 4-hydroxyphthalic anhydride and anhydrous DMF was 2:1.5:30, the mass ratio of nano-silica, anhydrous THF, modified liquid and deionized water was 3:45:16:6, and the mass ratio of carboxylated silica, p-toluenesulfonic acid, hydroxyphosphate compound and anhydrous DMF was 2:0.02:1.6:55; Step A3, ultrasonically disperse the esterification monomer in anhydrous DMF, control the ultrasonic frequency to 30kHz, the ultrasonic power to 500w, the ultrasonic wave for 30min, the speed to 500rpm, stir and heat to 64°C, then add triethylamine and toluene, add epichlorohydrin dropwise, control the dripping to be completed within 10min, maintain the speed unchanged, stir and react for 3h, filter after the reaction, control the rotary evaporation temperature to 82°C, rotary evaporate the filtrate to remove the anhydrous DMF, dissolve the rotary evaporation product in acetone, filter to remove triethylamine hydrochloride, control the rotary evaporation temperature to 40°C, and rotary evaporate the filtrate to remove acetone to obtain a functionalized binder, wherein the mass ratio of the esterification monomer, anhydrous DMF, triethylamine, toluene, epichlorohydrin and acetone is 42:520:2.8:6:22:320.
[0023] Preparation Example 5 This preparation example provides a method for preparing a functionalized binder, and the functionalized binder is prepared by the following steps: Step A1, stirring carbon tetrachloride and anhydrous THF at a rotation speed of 600 rpm for 30 minutes until uniform, adding dibutyl phosphite, and then adding triethylamine and diethanolamine under an ice-water bath, heating to 50° C., maintaining the rotation speed unchanged, stirring and reacting for 9 hours, filtering with suction, rotary distilling the filtrate, rotary distilling the filtrate until the anhydrous THF is removed, and controlling the rotary distillation temperature to 66° C. to obtain a hydroxy phosphate compound, wherein the mass ratio of carbon tetrachloride, anhydrous THF, dibutyl phosphite, triethylamine and diethanolamine is 65:35:6:2.0:4.6; Step A2, adding silane coupling agent KH-550 and 4-hydroxyphthalic anhydride to anhydrous THF, controlling the speed to 550rpm, stirring for 25min until uniform, heating to reflux, maintaining the speed unchanged, stirring for 5h to obtain a modified solution, ultrasonically dispersing nano-silicon dioxide in anhydrous THF, controlling the ultrasonic frequency to 40kHz, the ultrasonic power to 600w, ultrasonic for 30min, adding the modified solution and deionized water, heating to 54°C, stirring at a speed of 630rpm for 4.5h, after the stirring is completed, suction filtering, washing the filter cake with anhydrous ethanol and deionized water for 4 times, and drying at 55°C to constant weight to obtain carboxylated silica; adding carboxylated silica, p-toluenesulfonic acid and hydroxyphosphate compound to anhydrous D MF, the temperature was raised to 40°C, the speed was controlled to 700 rpm, and the mixture was stirred for 30 min until uniform, the speed was maintained constant, the temperature was raised to 76°C, the reaction was continued with stirring for 7 h, the rotary evaporation temperature was controlled to 82°C, the anhydrous DMF was removed by rotary evaporation, and then the mixture was washed with anhydrous ethanol and deionized water for 4 times, and dried at 60°C to constant weight to obtain an esterified monomer, wherein the mass ratio of silane coupling agent KH-550, 4-hydroxyphthalic anhydride and anhydrous DMF was 3:2.2:35, the mass ratio of nano-silica, anhydrous THF, modified liquid and deionized water was 4:50:18:7, and the mass ratio of carboxylated silica, p-toluenesulfonic acid, hydroxyphosphate compound and anhydrous DMF was 2.5:0.03:2.0:60; Step A3, ultrasonically disperse the esterification monomer in anhydrous DMF, control the ultrasonic frequency to 35kHz, the ultrasonic power to 550w, the ultrasonic for 35min, and the speed to 600rpm while stirring and heating to 66°C, then add triethylamine and toluene, and drop epichlorohydrin, control the dripping to be completed within 10min, and after the dripping is completed, stir and react for 3.5h. After the reaction is completed, filter, control the rotary evaporation temperature to 84°C, and rotary evaporate the filtrate to remove anhydrous DMF. The rotary evaporation product is placed in acetone and dissolved, and triethylamine hydrochloride is filtered to remove the triethylamine hydrochloride. The rotary evaporation temperature is controlled to 42°C, and the filtrate is rotary evaporated until the acetone is removed to obtain a functionalized binder, wherein the mass ratio of the esterification monomer, anhydrous DMF, triethylamine, toluene, epichlorohydrin and acetone is 53:580:3.7:9:24:340.
[0024] Preparation Example 6 This preparation example provides a method for preparing a functionalized binder, and the functionalized binder is prepared by the following steps: Step A1, stirring carbon tetrachloride and anhydrous THF at a rotation speed of 650 rpm for 35 min until uniform, adding dibutyl phosphite, adding triethylamine and diethanolamine under an ice-water bath, heating to 55° C., stirring and reacting for 10 h, filtering with suction, and rotary evaporating the filtrate to remove anhydrous THF, controlling the rotary evaporation temperature to 67° C. to obtain a hydroxy phosphate compound, wherein the mass ratio of carbon tetrachloride, anhydrous THF, dibutyl phosphite, triethylamine and diethanolamine is 70:40:7:2.2:5.4; Step A2, adding silane coupling agent KH-550 and 4-hydroxyphthalic anhydride to anhydrous THF, controlling the speed to 600 rpm, stirring for 30 minutes until uniform, heating to reflux, maintaining the speed unchanged, stirring for 6 hours to obtain a modified solution, ultrasonically dispersing nano-silicon dioxide in anhydrous THF, controlling the ultrasonic frequency to 30 kHz, the ultrasonic power to 500 w, ultrasonic for 40 minutes, adding the modified solution and deionized water, heating to 56 ° C, stirring at a speed of 610 rpm for 5 hours, after the stirring is completed, suction filtering, the filter cake is washed with anhydrous ethanol and deionized water for 5 times, and dried at 60 ° C to constant weight to obtain carboxylated silica; adding carboxylated silica, p-toluenesulfonic acid and hydroxyphosphate compound to anhydrous D MF, the temperature was raised to 45°C, the rotation speed was controlled to 750rpm, and the mixture was stirred for 35min until uniform, the rotation speed was maintained unchanged, the temperature was raised to 80°C, the reaction was continued with stirring for 8h, the rotary evaporation temperature was controlled to 82°C, the anhydrous DMF was removed by rotary evaporation, and then the mixture was washed with anhydrous ethanol and deionized water for 5 times in sequence, and dried at 65°C to constant weight to obtain an esterified monomer, wherein the mass ratio of silane coupling agent KH-550, 4-hydroxyphthalic anhydride and anhydrous DMF was 4:2.9:40, the mass ratio of nano-silica, anhydrous THF, modified liquid and deionized water was 5:55:20:8, and the mass ratio of carboxylated silica, p-toluenesulfonic acid, hydroxyphosphate compound and anhydrous DMF was 3:0.04:2.4:65; Step A3, ultrasonically disperse the esterification monomer in anhydrous DMF, control the ultrasonic frequency to 40kHz, the ultrasonic power to 600w, the ultrasonic for 40min, the speed to 700rpm, stir and heat to 68°C, then add triethylamine and toluene, add epichlorohydrin dropwise, control the dripping to be completed within 10min, after the dripping is completed, stir and react for 4h, after the reaction is completed, filter, control the rotary evaporation temperature to 86°C, rotary evaporate the filtrate to remove the anhydrous DMF, dissolve the rotary evaporation product in acetone, filter to remove triethylamine hydrochloride, control the rotary evaporation temperature to 44°C, and rotary evaporate the filtrate to remove acetone to obtain a functionalized binder, wherein the mass ratio of the esterification monomer, anhydrous DMF, triethylamine, toluene, epichlorohydrin and acetone is 64:640:4.6:12:26:360.
[0025] Comparative Preparation Example 2 This comparative preparation example provides a method for preparing a functionalized binder, and the functionalized binder is prepared by the following steps: Step A1, stirring carbon tetrachloride and anhydrous THF at a rotation speed of 550 rpm for 25 min until uniform, adding dibutyl maleate, and then adding triethylamine and diethanolamine under an ice-water bath, heating to 45° C., maintaining the rotation speed unchanged, stirring and reacting for 8 h, filtering with suction, and rotary evaporating the filtrate to remove anhydrous THF, controlling the rotary evaporation temperature to 65° C. to obtain a hydroxyphosphate compound, wherein the mass ratio of carbon tetrachloride, anhydrous THF, dibutyl maleate, triethylamine and diethanolamine is 60:30:5:1.8:3.8; Step A2, adding silane coupling agent KH-550 and 4-hydroxyphthalic anhydride to anhydrous THF, controlling the speed to 600 rpm, stirring for 20 minutes until uniform, heating to reflux, maintaining the speed unchanged, stirring and reacting for 4 hours to obtain a modified liquid, ultrasonically dispersing nano-silicon dioxide in anhydrous THF, controlling the ultrasonic frequency to 35 kHz, the ultrasonic power to 550 w, ultrasonic for 35 minutes, adding the modified liquid and deionized water, heating to 52° C., stirring at a speed of 650 rpm for 4 hours, after the stirring is completed, suction filtering, washing the filter cake with anhydrous ethanol and deionized water for 3 times, and drying at 50° C. to constant weight to obtain carboxylated silica; compounding carboxylated silica, p-toluenesulfonic acid and hydroxyphosphate The product was added into anhydrous DMF, heated to 35°C, the rotation speed was controlled to 650rpm, stirred for 25min until uniform, then heated to 72°C, continued to stir for 6h, the rotary evaporation temperature was controlled to 84°C, the filtrate was rotary evaporated to remove anhydrous DMF, and then washed with anhydrous ethanol and deionized water for 3 times, and dried at 55°C to constant weight, wherein the mass ratio of silane coupling agent KH-550, 4-hydroxyphthalic anhydride and anhydrous DMF was 2:1.5:30, the mass ratio of nano-silica, anhydrous THF, modified liquid and deionized water was 3:45:16:6, and the mass ratio of carboxylated silica, p-toluenesulfonic acid, hydroxyphosphate compound and anhydrous DMF was 2:0.02:1.6:55; Step A3, ultrasonically disperse the esterification monomer in anhydrous DMF, control the ultrasonic frequency to 30kHz, the ultrasonic power to 500w, the ultrasonic wave for 30min, the speed to 500rpm, stir and heat to 64°C, then add triethylamine and toluene, add epichlorohydrin dropwise, control the dripping to be completed within 10min, maintain the speed unchanged, stir and react for 3h, filter after the reaction, control the rotary evaporation temperature to 82°C, rotary evaporate the filtrate to remove the anhydrous DMF, dissolve the rotary evaporation product in acetone, filter to remove triethylamine hydrochloride, control the rotary evaporation temperature to 40°C, and rotary evaporate the filtrate to remove acetone to obtain a functionalized binder, wherein the mass ratio of the esterification monomer, anhydrous DMF, triethylamine, toluene, epichlorohydrin and acetone is 42:520:2.8:6:22:320.
[0026] Comparative Preparation Example 3 This comparative preparation example provides a method for preparing a functionalized binder, and the functionalized binder is prepared by the following steps: Step A1, stirring carbon tetrachloride and anhydrous THF at a rotation speed of 550 rpm for 25 minutes until uniform, adding dibutyl phosphite, and then adding triethylamine and diethanolamine under an ice-water bath, heating to 45° C., maintaining the rotation speed unchanged, stirring and reacting for 8 hours, filtering with suction, and rotary evaporating the filtrate to remove anhydrous THF, controlling the rotary evaporation temperature to 65° C. to obtain a hydroxy phosphate compound, wherein the mass ratio of carbon tetrachloride, anhydrous THF, dibutyl phosphite, triethylamine and diethanolamine is 60:30:5:1.8:3.8; Step A2, adding silane coupling agent KH-550 and 2-methylsuccinic anhydride to anhydrous THF, controlling the speed to 600 rpm, stirring for 20 minutes until uniform, heating to reflux, maintaining the speed unchanged, stirring and reacting for 4 hours to obtain a modified liquid, ultrasonically dispersing nano-silicon dioxide in anhydrous THF, controlling the ultrasonic frequency to 35 kHz, the ultrasonic power to 550 w, ultrasonic for 35 minutes, adding the modified liquid and deionized water, heating to 52 ° C, stirring at a speed of 650 rpm for 4 hours, after the stirring is completed, suction filtering, the filter cake is washed 3 times with anhydrous ethanol and deionized water, and dried at 50 ° C to constant weight to obtain carboxylated silica; adding carboxylated silica, p-toluenesulfonic acid and hydroxyphosphate compound In anhydrous DMF, the temperature was raised to 35°C, the rotation speed was controlled to 650rpm, and the mixture was stirred for 25min until uniform, and then the temperature was raised to 72°C, and the reaction was continued with stirring for 6h. The rotary evaporation temperature was controlled to 84°C, and the filtrate was subjected to rotary evaporation to remove anhydrous DMF, and then the mixture was washed with anhydrous ethanol and deionized water for 3 times in sequence, and dried at 55°C to constant weight to obtain an esterified monomer, wherein the mass ratio of silane coupling agent KH-550, 2-methylsuccinic anhydride and anhydrous DMF was 2:1.5:30, the mass ratio of nano-silica, anhydrous THF, modified liquid and deionized water was 3:45:16:6, and the mass ratio of carboxylated silica, p-toluenesulfonic acid, hydroxyphosphate compound and anhydrous DMF was 2:0.02:1.6:55; Step A3, ultrasonically disperse the esterification monomer in anhydrous DMF, control the ultrasonic frequency to 30kHz, the ultrasonic power to 500w, the ultrasonic wave for 30min, the speed to 500rpm, stir and heat to 64°C, then add triethylamine and toluene, add epichlorohydrin dropwise, control the dripping to be completed within 10min, maintain the speed unchanged, stir and react for 3h, filter after the reaction, control the rotary evaporation temperature to 82°C, rotary evaporate the filtrate to remove the anhydrous DMF, dissolve the rotary evaporation product in acetone, filter to remove triethylamine hydrochloride, control the rotary evaporation temperature to 40°C, and rotary evaporate the filtrate to remove acetone to obtain a functionalized binder, wherein the mass ratio of the esterification monomer, anhydrous DMF, triethylamine, toluene, epichlorohydrin and acetone is 42:520:2.8:6:22:320.
[0027] Comparative Preparation Example 4 This comparative preparation example provides a method for preparing a functionalized binder, and the functionalized binder is prepared by the following steps: Step A1, stirring carbon tetrachloride and anhydrous THF at a rotation speed of 550 rpm for 25 minutes until uniform, adding dibutyl phosphite, and then adding triethylamine and diethanolamine under an ice-water bath, heating to 45° C., maintaining the rotation speed unchanged, stirring and reacting for 8 hours, filtering with suction, and rotary evaporating the filtrate to remove anhydrous THF, controlling the rotary evaporation temperature to 65° C. to obtain a hydroxy phosphate compound, wherein the mass ratio of carbon tetrachloride, anhydrous THF, dibutyl phosphite, triethylamine and diethanolamine is 60:30:5:1.8:3.8; Step A2, adding silane coupling agent KH-550 and 4-hydroxyphthalic anhydride to anhydrous THF, controlling the speed to 600 rpm, stirring for 20 minutes until uniform, heating to reflux, maintaining the speed unchanged, stirring for 4 hours to obtain a modified liquid, ultrasonically dispersing nano-silicon dioxide in anhydrous THF, controlling the ultrasonic frequency to 35 kHz, the ultrasonic power to 550 w, ultrasonic for 35 minutes, adding the modified liquid and deionized water, heating to 52 ° C, stirring at a speed of 650 rpm for 4 hours, after the stirring is completed, suction filtering, the filter cake is washed 3 times with anhydrous ethanol and deionized water, and dried at 50 ° C to constant weight to obtain carboxylated silica; adding carboxylated silica, p-toluenesulfonic acid and hydroxyphosphate compound In anhydrous DMF, the temperature was raised to 35°C, the rotation speed was controlled to 650rpm, and the mixture was stirred for 25min until uniform, and then the temperature was raised to 72°C, and the reaction was continued with stirring for 6h. The rotary evaporation temperature was controlled to 84°C, and the filtrate was subjected to rotary evaporation to remove anhydrous DMF, and then the mixture was washed with anhydrous ethanol and deionized water for 3 times in sequence, and dried at 55°C to constant weight to obtain an esterified monomer, wherein the mass ratio of silane coupling agent KH-550, 4-hydroxyphthalic anhydride and anhydrous DMF was 2:1.5:30, the mass ratio of nano-silica, anhydrous THF, modified liquid and deionized water was 3:45:16:6, and the mass ratio of carboxylated silica, p-toluenesulfonic acid, hydroxyphosphate compound and anhydrous DMF was 2:0.02:1.6:55; Step A3, ultrasonically disperse the esterification monomer in anhydrous DMF, control the ultrasonic frequency to 30kHz, the ultrasonic power to 500w, the ultrasonic wave to 30min, the speed to 500rpm, stir and heat to 64°C, then add triethylamine and toluene, add 2-chloropropane dropwise, control the dripping to be completed within 10min, maintain the speed unchanged, stir and react for 3h, filter after the reaction, control the rotary evaporation temperature to 82°C, rotary evaporate the filtrate to remove the anhydrous DMF, dissolve the rotary evaporation product in acetone, filter to remove triethylamine hydrochloride, control the rotary evaporation temperature to 40°C, and rotary evaporate the filtrate to remove acetone to obtain a functionalized binder, wherein the mass ratio of the esterification monomer, anhydrous DMF, triethylamine, toluene, 2-chloropropane and acetone is 42:520:2.8:6:22:320.
[0028] Examples 1-3 and Comparative Examples 1-4 provide environmentally friendly high-strength thermal insulation castables for coke oven bottoms.
[0029] Example 1 This embodiment provides an environmentally friendly high-strength thermal insulation castable for a coke oven bottom. The environmentally friendly high-strength thermal insulation castable for a coke oven bottom is prepared by the following steps: Step S1, preparing the following raw materials by weight: 40 parts of mullite porous clinker, 8 parts of ultrafine silica powder, 12 parts of CA-60 aluminate cement, 2 parts of deionized water, and 0.2 parts of an admixture, wherein the admixture is composed of the functionalized binder prepared in Preparation Example 4 and the modified carbon fiber prepared in Preparation Example 1, the functionalized binder accounts for 72%, and the rest is the modified carbon fiber; Step S2, pressure molding: Mullite porous clinker, ultrafine silica powder and CA-60 aluminate cement are stirred at 1100 rpm for 3 min until mixed, deionized water is added, the speed is adjusted to 600 rpm and stirred for 20 min until mixed, admixtures are added, the speed is maintained unchanged, stirring is continued for 12 min, pressure molding is performed, and then placed at a temperature of 25°C and a relative humidity of 95% RH for 2 days, and then baked at 110°C for 36 hours to obtain an environmentally friendly high-strength coke oven bottom insulation castable, wherein the pressure of the pressure molding is 150kg / m 2 The pressing time is 10s.
[0030] Example 2 This embodiment provides an environmentally friendly high-strength thermal insulation castable for a coke oven bottom. The environmentally friendly high-strength thermal insulation castable for a coke oven bottom is prepared by the following steps: Step S1, preparing the following raw materials by weight: 45 parts of mullite porous clinker, 9 parts of ultrafine silica powder, 14 parts of CA-60 aluminate cement, 4 parts of deionized water, and 0.3 parts of an admixture, wherein the admixture is composed of the functionalized binder prepared in Preparation Example 5 and the modified carbon fiber prepared in Preparation Example 2, the functionalized binder accounts for 78%, and the rest is the modified carbon fiber; Step S2, pressure molding: Mullite porous clinker, ultrafine silica powder and CA-60 aluminate cement are stirred at 1200 rpm for 4 minutes until mixed, deionized water is added, the speed is adjusted to 700 rpm and stirred for 22 minutes until mixed, admixtures are added, the speed is maintained unchanged, stirring is continued for 14 minutes, pressure molding is performed, and then placed at a temperature of 25°C and a relative humidity of 95% RH for 2.5 days, and then baked at 115°C for 42 hours to obtain an environmentally friendly high-strength coke oven bottom insulation castable, wherein the pressure of the pressure molding is 165kg / m 2 The pressing time is 15s.
[0031] Example 3 This embodiment provides an environmentally friendly high-strength thermal insulation castable for a coke oven bottom. The environmentally friendly high-strength thermal insulation castable for a coke oven bottom is prepared by the following steps: Step S1, preparing the following raw materials by weight: 50 parts of mullite porous clinker, 10 parts of ultrafine silica powder, 16 parts of CA-60 aluminate cement, 6 parts of deionized water, and 0.4 parts of an admixture, wherein the admixture is composed of the functionalized binder prepared in Preparation Example 6 and the modified carbon fiber prepared in Preparation Example 3, the functionalized binder accounts for 84%, and the rest is the modified carbon fiber; Step S2, pressure molding: Mullite porous clinker, ultrafine silica powder and CA-60 aluminate cement are stirred at 1300 rpm for 5 minutes until mixed, deionized water is added, the speed is adjusted to 800 rpm and stirred for 24 minutes until mixed, admixtures are added, the speed is maintained unchanged, stirring is continued for 16 minutes, pressure molding is performed, and then placed at a temperature of 25°C and a relative humidity of 95% RH for 3 days, and then baked at 120°C for 48 hours to obtain an environmentally friendly high-strength coke oven bottom insulation castable, wherein the pressure of the pressure molding is 180kg / m 2 The pressing time is 20s.
[0032] Comparative Example 1 This comparative example provides an environmentally friendly high-strength thermal insulation castable for a coke oven bottom, and the environmentally friendly high-strength thermal insulation castable for a coke oven bottom is prepared by the following steps: Step S1, preparing the following raw materials by weight: 40 parts of mullite porous clinker, 8 parts of ultrafine silica powder, 12 parts of CA-60 aluminate cement, 2 parts of deionized water, and 0.2 parts of an admixture, wherein the admixture is composed of the functionalized binder prepared in Preparation Example 4 and the modified carbon fiber prepared in Comparative Preparation Example 1, the functionalized binder accounts for 72%, and the rest is the modified carbon fiber; Step S2, pressure molding: Mullite porous clinker, ultrafine silica powder and CA-60 aluminate cement are stirred at 1100 rpm for 3 min until mixed, deionized water is added, the speed is adjusted to 600 rpm and stirred for 20 min until mixed, admixtures are added, the speed is maintained unchanged, stirring is continued for 12 min, pressure molding is performed, and then placed at a temperature of 25°C and a relative humidity of 95% RH for 2 days, and then baked at 110°C for 36 hours to obtain an environmentally friendly high-strength coke oven bottom insulation castable, wherein the pressure of the pressure molding is 150kg / m 2 The pressing time is 10s.
[0033] Comparative Example 2 This comparative example provides an environmentally friendly high-strength thermal insulation castable for a coke oven bottom, and the environmentally friendly high-strength thermal insulation castable for a coke oven bottom is prepared by the following steps: Step S1, preparing the following raw materials by weight: 40 parts of mullite porous clinker, 8 parts of ultrafine silica powder, 12 parts of CA-60 aluminate cement, 2 parts of deionized water, and 0.2 parts of admixture, wherein the admixture is composed of the functionalized binder prepared in Comparative Preparation Example 2 and the modified carbon fiber prepared in Preparation Example 1, the functionalized binder accounts for 72%, and the rest is modified carbon fiber; Step S2, pressure molding: Mullite porous clinker, ultrafine silica powder and CA-60 aluminate cement are stirred at 1100 rpm for 3 min until mixed, deionized water is added, the speed is adjusted to 600 rpm and stirred for 20 min until mixed, admixtures are added, the speed is maintained unchanged, stirring is continued for 12 min, pressure molding is performed, and then placed at a temperature of 25°C and a relative humidity of 95% RH for 2 days, and then baked at 110°C for 36 hours to obtain an environmentally friendly high-strength coke oven bottom insulation castable, wherein the pressure of the pressure molding is 150kg / m 2 The pressing time is 10s.
[0034] Comparative Example 3 This comparative example provides an environmentally friendly high-strength thermal insulation castable for a coke oven bottom, and the environmentally friendly high-strength thermal insulation castable for a coke oven bottom is prepared by the following steps: Step S1, preparing the following raw materials by weight: 40 parts of mullite porous clinker, 8 parts of ultrafine silica powder, 12 parts of CA-60 aluminate cement, 2 parts of deionized water, and 0.2 parts of admixture, wherein the admixture is composed of the functionalized binder prepared in Comparative Preparation Example 3 and the modified carbon fiber prepared in Preparation Example 1, the functionalized binder accounts for 72%, and the rest is modified carbon fiber; Step S2, pressure molding: Mullite porous clinker, ultrafine silica powder and CA-60 aluminate cement are stirred at 1100 rpm for 3 min until mixed, deionized water is added, the speed is adjusted to 600 rpm and stirred for 20 min until mixed, admixtures are added, the speed is maintained unchanged, stirring is continued for 12 min, pressure molding is performed, and then placed at a temperature of 25°C and a relative humidity of 95% RH for 2 days, and then baked at 110°C for 36 hours to obtain an environmentally friendly high-strength coke oven bottom insulation castable, wherein the pressure of the pressure molding is 150kg / m 2 The pressing time is 10s.
[0035] Comparative Example 4 This comparative example provides an environmentally friendly high-strength thermal insulation castable for a coke oven bottom, and the environmentally friendly high-strength thermal insulation castable for a coke oven bottom is prepared by the following steps: Step S1, preparing the following raw materials by weight: 40 parts of mullite porous clinker, 8 parts of ultrafine silica powder, 12 parts of CA-60 aluminate cement, 2 parts of deionized water, and 0.2 parts of admixture, wherein the admixture is composed of the functionalized binder prepared in Comparative Preparation Example 4 and the modified carbon fiber prepared in Preparation Example 1, the functionalized binder accounts for 72%, and the rest is modified carbon fiber; Step S2, pressure molding: Mullite porous clinker, ultrafine silica powder and CA-60 aluminate cement are stirred at 1100 rpm for 3 min until mixed, deionized water is added, the speed is adjusted to 600 rpm and stirred for 20 min until mixed, admixtures are added, the speed is maintained unchanged, stirring is continued for 12 min, pressure molding is performed, and then placed at a temperature of 25°C and a relative humidity of 95% RH for 2 days, and then baked at 110°C for 36 hours to obtain an environmentally friendly high-strength coke oven bottom insulation castable, wherein the pressure of the pressure molding is 150kg / m 2 The pressing time is 10s.
[0036] Performance Testing The flexural strength is tested according to GB / T3001-2007; the compressive strength is tested according to GB / T5072-2008; the thermal conductivity is tested according to GB / T 10294-2008 standard, as shown in Table 1; Table 1 Mechanical strength and thermal conductivity test of thermal insulation castables obtained in Examples 1-3 and Comparative Examples 1-4
[0037] It can be seen from Table 1 that compared with Comparative Examples 1-4, the environmentally friendly high-strength coke oven bottom insulation castable used in Examples 1-3 has better flexural strength and higher flexural strength, and lower thermal conductivity, which indicates that the insulation castable prepared in the present application has better mechanical strength and thermal insulation performance.
[0038] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. Environmentally friendly high-strength thermal insulation castable for coke oven bottom, characterized in that: Prepared by the following steps: Step S1, prepare the following raw materials in parts by weight: 40-50 parts of mullite porous clinker, 8-10 parts of ultrafine silica powder, 12-16 parts of aluminate cement, 2-6 parts of deionized water, and 0.2-0.4 parts of admixture; Step S2, pressure molding: Mullite porous clinker, ultrafine silica powder and aluminate cement are mixed, deionized water is added, stirred evenly, admixtures are added, stirring is continued for 12-16 minutes, pressure molding is performed, curing is performed, and baking is performed to obtain an environmentally friendly high-strength thermal insulation castable for coke oven bottom; The admixture is composed of a functionalized binder and modified carbon fibers, wherein the functionalized binder accounts for 72-84% and the rest is modified carbon fibers; The functionalized binder is firstly prepared by subjecting dibutyl phosphite and diethanolamine to Michael addition reaction to obtain a hydroxy phosphate compound, then undergoing an esterification reaction with carboxylated silica to obtain an esterified monomer, and finally undergoing a nucleophilic substitution reaction with epichlorohydrin to obtain the functionalized binder; The carboxylated silica is firstly prepared by a ring-opening esterification reaction of silane coupling agent KH-550 and 4-hydroxyphthalic anhydride to obtain a modified liquid, and then chemically cross-linked with nano-silicon dioxide to obtain the modified liquid. The modified carbon fiber is firstly prepared by treating the carbon fiber with acetone to obtain pretreated carbon fiber, and then undergoing oxidation reaction with nitric acid aqueous solution.
2. The environmentally friendly high-strength thermal insulation castable for coke oven bottom according to claim 1, characterized in that: The functionalized binder is prepared by the following steps: Step A1, mix carbon tetrachloride and anhydrous THF evenly, add dibutyl phosphite, add triethylamine and diethanolamine under ice-water bath, raise the temperature to 45-55° C., stir and react for 8-10 hours, filter with suction, and rotary evaporate the filtrate to obtain a hydroxy phosphate compound; Step A2, adding silane coupling agent KH-550 and 4-hydroxyphthalic anhydride to anhydrous THF, stirring evenly, heating to reflux, stirring and reacting for 4-6 hours to obtain a modified liquid, ultrasonically dispersing nano-silicon dioxide in anhydrous THF, adding the modified liquid and deionized water, heating to 52-56° C., stirring for 4-5 hours, after the stirring is completed, suction filtering, washing the filter cake, and drying to obtain carboxylated silicon dioxide; adding carboxylated silicon dioxide, p-toluenesulfonic acid and hydroxyphosphate compound to anhydrous DMF, heating to 35-45° C., stirring evenly, then heating to 72-80° C., continuing to stir and react for 6-8 hours, rotary evaporation, washing, and drying to obtain an esterification monomer; Step A3, ultrasonically disperse the esterification monomer in anhydrous DMF, raise the temperature to 64-68°C while stirring, then add triethylamine and toluene, add epichlorohydrin dropwise, stir and react for 3-4 hours after the addition is completed, filter, rotary evaporate, dissolve the rotary evaporated product in acetone, filter, and rotary evaporate the filtrate to obtain a functionalized binder.
3. The environmentally friendly high-strength thermal insulation castable for coke oven bottom according to claim 2, characterized in that: In the step A1, the mass ratio of carbon tetrachloride, anhydrous THF, dibutyl phosphite, triethylamine and diethanolamine is 60-70:30-40:5-7:1.8-2.2:3.8-5.
4.
4. The environmentally friendly high-strength thermal insulation castable for coke oven bottom according to claim 2, characterized in that: In the step A2, the mass ratio of silane coupling agent KH-550, 4-hydroxyphthalic anhydride and anhydrous DMF is 2-4:1.5-2.9:30-40, the mass ratio of nano-silica, anhydrous THF, modified liquid and deionized water is 3-5:45-55:16-20:6-8, and the mass ratio of carboxylated silica, p-toluenesulfonic acid, hydroxyphosphate compound and anhydrous DMF is 2-3:0.02-0.04:1.6-2.4:55-65.
5. The environmentally friendly high-strength thermal insulation castable for coke oven bottom according to claim 2, characterized in that: In the step A3, the mass ratio of the esterification monomer, anhydrous DMF, triethylamine, toluene, epichlorohydrin and acetone is 42-64: 520-640: 2.8-4.6: 6-12: 22-26: 320-360.
6. The environmentally friendly high-strength thermal insulation castable for coke oven bottom according to claim 1, characterized in that: The modified carbon fiber is prepared by the following steps: The carbon fiber is placed in acetone, stirred at 45-55°C for 8-12 hours, taken out, and washed to obtain pretreated carbon fiber. The pretreated carbon fiber is placed in a nitric acid aqueous solution, stirred at 80-90°C for 2-3 hours, filtered, and the filter cake is washed to obtain modified carbon fiber.
7. The environmentally friendly high-strength thermal insulation castable for coke oven bottom according to claim 6, characterized in that: The mass ratio of the carbon fiber to acetone is 3-5:40, and the mass ratio of the pretreated carbon fiber to concentrated nitric acid is 5:50-60.
8. The environmentally friendly high-strength thermal insulation castable for coke oven bottom according to claim 1, characterized in that: In the step S1, the particle size of the ultrafine silicon powder is ≤0.015 mm.
9. The environmentally friendly high-strength thermal insulation castable for coke oven bottom according to claim 1, characterized in that: The pressure of the pressurized molding is 150-180 kg / m 2 ; The pressure molding time is 10-20s.
Citation Information
Patent Citations
Low-iron low-aluminum mullite brick for coke oven and preparation method thereof
CN107032811A
Semi-lightweight steel ladle permanent layer castable and method for preparing steel ladle permanent layer therefrom
CN110655391A
Alumina-based cordierite explosion-proof castable
CN113698186A
Special castable for kilneye of cement kiln
CN113979757A
Coke oven wall thermal-state plastering refractory mortar as well as preparation method and application thereof
CN114516760A
Cited By
Preparation method and application of partially neutralized sodium polyacrylate
CN120463845A